FACTORS OF DEVELOPMENT OF EQUESTRIAN CLUBS IN CONDITIONS OF CHANGEABLE NECESSITIES OF POPULATION - Shmarenkova, Natalia (Global Prosperity, 2021)
The article deals with the systematization of the development factors of equestrian clubs in the conditions of changing needs of the population. The study categorized the main features by which scientists identify these factors, in particular, identified three scientific approaches (the division of factors into external and internal, depending on changes in the demand for equestrian sports, leisure in this area, the division of factors into zootechnical, technical and personnel). Guided by the leading scientific approaches, a universal approach to the list of factors of development of equestrian clubs under the changing needs of the population is formulated. The author noted that the above list provides for: external factors of influence (investment; market; price; political (or military-political); economic; financial-credit; legislative; institutional; promotion of business environment; zootechnical (level of development of veterinary service, institutions in the field of health of horses at the level of territories, regions, countries)); internal factors of influence (economic (high or low level of economic development of the subjects of activity); personnel (low or high level of internal personnel support); low level of management, marketing); zootechnical and technical (high or low level)). Thus, the author established for the first time a universal definition of the main factors influencing the development of modern equestrian clubs in the conditions of changing population needs, taking into account the current state of functioning of the studied institutions and the views of scientists on the mentioned issues. This list is based on the division of these factors into internal and external. The main elements of influence on the status and development of modern equestrian clubs in the existing directions are distinguished.